Syrian Arab Republic : 2006 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Non-oil GDP growth in Syria may have risen to about 5 1\2 percent in 2005, from 5 percent in 2004, buoyed by business investment and supported by household consumption and non-oil exports. Private consumption was boosted by rapid credit growth, a boom in real estate prices triggered by capital inflows, and the large wage increase from mid-2004. Overall, net non-oil exports contributed positively to growth and to an improvement in the non-oil current account deficit, thereby helping to maintain external balance despite the sharp decline in net oil exports.